On some destructive fishing methods of Central Travancore of Kerala, India - Mathews Plamoottil and Than Win (Journal of Zoological and Bioscience Research, 2017)
Many destructive fishing practices are widely used at many sites of Central Travancore of Kerala, India. Most of these are indigenous methods practiced at high level to low level regions. It includes chemical poisons, plant poisons, fish traps, electric fishing etc. All these gears kill the fishes and their fries and fingerlings indiscriminately. It is an endeavor to trace out the details of these harmful fishing methods.